Integrating a simulation model as an architectural component of a game - Koscianski, André; Abreu, Guilherme T. S.; Padilha, Luiz G. M. (Anais Estendidos do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2022)
Many computer games involve the simulation of real-world phenomena, mechanisms, and behavior of beings. Examples vary from simple Physics found in the platform style to characters that learn and adapt according to user choices. Another field that uses computer models is criminology, a theme that is also a starting point for many games. This paper studies the integration of a (serious) criminal simulation model and a computer game, keeping the two perspectives separated; the model functions as an add-on that reshapes parts of the game.